2008
DOI: 10.1016/j.ypmed.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple health behavior change research: An introduction and overview

Abstract: In 2002, the Society of Behavioral Medicine's special interest group on Multiple Health Behavior Change was formed. The group focuses on the interrelationships among health behaviors and interventions designed to promote change in more than one health behavior at a time. Growing evidence suggests the potential for multiple-behavior interventions to have a greater impact on public health than single-behavior interventions. However, there exists surprisingly little understanding of some very basic principles con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
428
3
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 516 publications
(464 citation statements)
references
References 73 publications
(43 reference statements)
12
428
3
10
Order By: Relevance
“…The health behaviors included both adoption (e.g., physical activity) and cessation behaviors (e.g., smoking cessation). As the MHBC field is relatively young [24], the focus was on papers from 2006 to 2011. We included studies with older adults (>55+) from community and clinical settings.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…The health behaviors included both adoption (e.g., physical activity) and cessation behaviors (e.g., smoking cessation). As the MHBC field is relatively young [24], the focus was on papers from 2006 to 2011. We included studies with older adults (>55+) from community and clinical settings.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Such an undertaking requires balancing several concepts such as participant burden for multiple assessments, prioritizing the presentation of multiple behavior strategies, etc. Researchers have concluded that multiple simultaneous behavior change interventions are promising for addictive behaviors and for multiple cancer prevention behaviors including diet, physical activity, and obesity prevention [18][19][20][21][22][23][24]. In this Special Section, Velicer et al [25] describe a large intervention trial that examined the effectiveness of two different computer-delivered interventions designed to influence multiple behaviors in middle school students: The first intervention targeted multiple substance use behaviors; the other targeted energy balance behaviors.…”
mentioning
confidence: 99%
“…In addition, previous research has shown that we cannot assume that all children who eat healthily are also sufficiently physically active and vice versa (11) . Consequently, a better understanding of clustering of multiple health behaviours in young people is needed to inform effective interventions (4,12) . Cluster analysis is frequently used in health research to identify mutually exclusive, homogeneous groups of individuals sharing numerous characteristics.…”
mentioning
confidence: 99%